Using Video-Reflexive Ethnography to Engage Hospital Staff to Improve Dementia Care. (6th July 2018) - Hung, Lillian; Phinney, Alison; Chaudhury, Habib; Rodney, Paddy
In this article, we discuss how video-reflexive ethnography may be useful in engaging staff to improve dementia care in a hospital medical unit. Seven patients with dementia were involved in the production of patient-story videos, and fifty members of staff (nurses, physicians, and allied health practitioners) participated in video-reflexive groups. We identified five substantial themes to describe how video-reflexive groups might contribute to enacting person-centered care for improving dementia care: (a) seeing through patients' eyes, (b) seeing normal strange and surprised, (c) seeing inside and between, (d) seeing with others inspires actions, and (e) seeing with the team builds a culture of learning. Our findings suggest that video reflexivity is not only useful for staff engagement but also effective in enhancing team capacity to enact person-centered care in the hospital setting.